PETDULI: Robust Pet-Shop Marketplace Modeling using Design Thinking Method - Ziyad Muhammad Zain Soti; Irianto, Kurniawan D (International Journal of Informatics and Computation, 2025)
This study employs the Design Thinking methodology to construct a prototype for discovering pet shops. In this study, we gathered data through interviews to uncover key pain points; insights from these interviews informed the definition phase. During ideation, low and high-fidelity wireframes and user flows were created to guide the development of a functional prototype. This study obtained a SUS score of 81.17, indicating excellent overall satisfaction. The findings highlight that simplified product search, simplified service search, clear service categorization, and intuitive location-based search significantly enhance overall user experience. This paper concluded with actionable design guidelines for practitioners aiming to improve discoverability and usability in pet shop e-commerce platforms.